Can the 128-Hz tuning fork be an alternative to the biothesiometer for diabetic peripheral neuropathy screening? A cross-sectional study in a tertiary hospital in East India - Soumik Goswami; Sujaya Chattopadhyay; Nilanjan Sengupta; Arjun Baidya (BMJ Open)
Introduction Diabetic neuropathy is frequently underdiagnosed and undertreated. Logistic problems accompany the routine use of the biothesiometer. Hence, we attempted to find a more easily available alternative.Research design and methods 149 patients with diabetes visiting the outpatient endocrinology clinic were assessed for vibration sense using a 128-Hz tuning fork (absolute timing method) and a biothesiometer. A reading of >25 V on the biothesiometer (known as vibration perception threshold or VPT) was taken as the diagnostic criterion for severe neuropathy while >15 V was used as an indicator of the mild form. The sensitivity and specificity were calculated by constructing the receiver operating characteristic curve (ROC). A p value of <0.05 was considered as statistically significant.Results The timed tuning fork (TTF) test showed a statistically significant correlation with the VPT measurements (r=−0.5, p=0.000). Using the VPT findings as a reference, a timed tuning fork cut-off of 4.8 s was 76% sensitive and 77% specific in diagnosing mild neuropathy while absent tuning fork sensation demonstrated 70% sensitivity and 90% specificity in detecting severe neuropathy.Conclusions The tuning fork test demonstrated significant sensitivity and specificity in diagnosing diabetic peripheral neuropathy when compared against the biothesiometer. A cut-off of 4.8 s can be a useful indicator of the early stages of onset of the condition.